The subtle red line between combating and resolving inflammation in the cardiovascular disease, a “silent sniper” - Ciarán Kennedy; Luke J Conroy; Braden Millar; Monica de Gaetano (Bleeding, Thrombosis and Vascular Biology)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide. Despite advancements in medical interventions, the burden of CVD continues to rise due to aging populations, lifestyle factors, and socio-economic disparities. Chronic inflammation plays a pivotal role in CVD pathogenesis, particularly in atherosclerosis, where macrophage polarization influences disease progression. Pharmacological strategies targeting lipid metabolism have evolved beyond statins to include novel therapeutics, such as PCSK9 inhibitors, ezetimibe, and bempedoic acid, offering alternative solutions for statin-intolerant individuals. Precision medicine in CVD harnesses genetic and omics data to personalize risk assessment, guide therapy, and improve outcomes, particularly through targeting genetic variants, inflammation, and clonal haematopoiesis. Additionally, gene-editing technologies, like CRISPR-Cas9, hold promise for addressing genetic contributors to CVD by modulating key regulatory targets, such as PCSK9 and ANGPTL3, potentially providing long-term solutions to hyperlipidaemia. Recent evidence suggests that glucose-lowering medications, including SGLT2 inhibitors and GLP-1 receptor agonists, confer cardiovascular benefits beyond glycaemic control by reducing inflammation, improving endothelial function, and promoting macrophage phenotype switching. Emerging therapies, such as GLP-1/GIP dual agonists, may offer superior cardioprotective effects, but further clinical trials are required to validate their efficacy in CVD. Anti-inflammatory treatments, including IL-1β inhibitors, colchicine, and statins, have demonstrated efficacy in reducing cardiovascular events. However, their broad immunosuppressive effects present challenges. Resolution pharmacology, focusing on specialized pro-resolving lipid mediators (SPMs), represents a novel therapeutic approach aimed at restoring immune balance, in lieu of merely suppressing inflammation. Understanding macrophage-driven inflammation in CVD could revolutionize treatment paradigms, shifting toward targeted interventions that resolve, rather than inhibit, inflammatory processes. Overall, integrating lipid-lowering therapies, gene editing, glucose-modulating drugs, and inflammation-resolution strategies offers a multi-faceted approach to mitigating CVD risk and improving long-term patient outcomes.